2017
DOI: 10.5603/gp.a2017.0121
|View full text |Cite
|
Sign up to set email alerts
|

Dydrogesterone has no effect on uterine fibroids when used to prevent miscarriage in pregnant women with uterine fibroids

Abstract: Objectives: To analyse the effect of dydrogesterone use during pregnancy on uterine fibroids, pregnancy complications, and pregnancy outcome. Material and methods:In all, 372 pregnant women with uterine fibroids who were treated at the Affiliated Provincial Hospital of Shandong University were included in this study. Thirty-three of these women received dydrogesterone and constituted the treatment group, and the 27 women who were found to have uterine fibroids during the first trimester but did not receive int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…Western medicine mostly uses progesterone supplementation to treat pregnant women with threatened abortion. Dydrogesterone tablets are commonly used clinically to supplement progesterone, which can promote the secretion of chorionic gonadotropin and endogenous progesterone, increase the endocrine activity of placental trophoblast, reduce the level of oxytocin, and antagonize the stimulation of uterus by prostaglandins, thus inhibiting uterine contractions and maintaining pregnancy [ 13 , 14 ]. Some scholars have reported that oral dydrogesterone is effective in the treatment of threatened abortion with a low abortion rate and no congenital malformation [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Western medicine mostly uses progesterone supplementation to treat pregnant women with threatened abortion. Dydrogesterone tablets are commonly used clinically to supplement progesterone, which can promote the secretion of chorionic gonadotropin and endogenous progesterone, increase the endocrine activity of placental trophoblast, reduce the level of oxytocin, and antagonize the stimulation of uterus by prostaglandins, thus inhibiting uterine contractions and maintaining pregnancy [ 13 , 14 ]. Some scholars have reported that oral dydrogesterone is effective in the treatment of threatened abortion with a low abortion rate and no congenital malformation [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, its vaginal form is superior to the oral form; although it reaches a faster plasma peak level in oral intake, more constant drug concentrations are observed in vaginal use [16,17]. Progesterone is effectively used for the prevention of threatened miscarriage, preterm labor, preterm birth in women with a short cervix, luteal deficiency, and recurrent miscarriage [18][19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%